A journalism of humanity a candid history of the world's first journalism school - Weinberg, Steve (University of Missouri Press, 2008)
"Founded by Walter Williams, a newsman who lacked a college education, the University of Missouri's School of Journalism is regarded as among the best in the world. Weinberg uncovers the history of the school's first 100 years, revealing the flaws as well as the virtues of the Missouri Method"--Provided by publisher.